Analisis SOAR Dalam Strategi Pengembangan Program Feeder Wira-Wiri di Kota Surabaya - Yovi Arif Zachary; Agus Widiyarta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The background of this research is based on the chronic congestion problem in Surabaya City and the low accessibility of public transportation to residential areas and community activity centers. The Wira-Wiri Feeder Program is present as a feeder transportation solution that reaches narrow streets and is integrated with other public transportation systems such as Suroboyo Bus. Therefore, this study aims to describe and analyze the development strategy of the Wira-Wiri Feeder Program in Surabaya City using the SOAR approach. This research method uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that the main strengths of the Wira-Wiri Feeder program lie in accessibility and system integration, opportunities in the form of community enthusiasm and policy support, aspirations to expand service coverage, and the results achieved in increasing the number of public transportation users. However, there are still challenges such as limited budget, fleet, and public preference for private vehicles. Through SOAR analysis, this research recommends strengthening strategies based on internal advantages and external opportunities to realize a sustainable transportation system in Surabaya City.